Analisis Metode K-Means Clustering Dalam Pengelompokan Penjualan Sembako - Fikria, Rahma; Sriani, Sriani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research aims to analyze the clustering of staple food sales at PT. Sinarmas Distribusi Nusantara using the K-Means Clustering method. The main problem faced by the company is the lack of clarity in identifying which products have high sales performance and which products require more attention. This issue negatively impacts the effectiveness of the company's marketing and distribution strategies. The K-Means Clustering method is used to divide the sales data of staple food products into several clusters based on the similarity of their characteristics. Sales data is collected and analyzed to group products based on their sales levels. The research results show that out of all the products studied, 5 products fall into the